Efecto de la temperatura sobre el ciclo de desarrollo de Lucilia sericata (Meigen) (Diptera: Calliphoridae) en condiciones de laboratorio - ARGOMEDO PAJUELO, Jonathan Jairo (2019)
The objective, was determine the effect of the temperature over the development of Lucilia sericata (Meigen) conditions of laboratory. It used a necrotrap with liver of fresh beef like bart. It collected old species for the determination taxonomica with codes specialist, as well as gravid female that was took to the laboratory of Entomologia of the National University of Trujillo for the obtention of stance. The breed from egg to old it did through a design of three treatment and three repetitions, for what it prepared nine wood boxes with 120 eggs over 200 gr of beef liver to 15, 20 and 25ºC, with a roon of mistake of ±0.5ºC and a humidity relative of 69 to 72%. The take of information it did with a thermo-hygrometer for each treatment and it did measure of length and diameter of the different phases of the cycle of development through the tool “Axiovisión”. The analysis of information it did with the analysis of variance and the test of Tukey, with a level of mean of the 0.05. It found a average of duration of the cycle of development of L. sericata of 1 028, 473 and 307 hours, and the length and diameter maximum for the phase larval post- feeding was from 11.97 and 2.69mm, 13.89 and 2.88mm, and 14.92 and 3.10mm to 15, 20 and 25ºC respectively.